Narrative Disorientation and Beckett's Bureaucratic Space. Issue 2 (September 2020) - McAllister, Brian J.
Abstract : This essay investigates political implications of narrative space in Samuel Beckett's closed-space narratives, arguing for a narratological understanding of these spatial politics. It focuses on Imagination Dead Imagine, a text that radically disorients reader engagement with narrative space. In this text, Beckett collides bureaucratic narrative logic, which compartmentalises and accounts for all details of narrative space, against trenchantly anti-bureaucratic grammar, in which sentence structure disrupts and undermines spatial ordering. This dialectical relationship between bureaucratic narrative voice and unstable grammar critiques the logic that, in Giorgio Agamben's biopolitical sense, defines the bureaucratic nation-state. By associating narrative space and its inhabiting characters with the bureaucratic logic of modernity, Imagination Dead Imagine enacts and examines what Agamben calls the state of exception, inscribing politics onto the bare life of characters. While the text avoids direct reference to these historical conditions, its structure performs and resists the politics implicit in those conditions.